Theoretical Approach on the Comparison between the Oxidative Dehydrogenation of Amines and MOF Mediated Amine Oxidation - Macías Torres, Moisés Abraham (2022)
Oxidative dehydrogenation play an important role in the production of raw materials for chemical, petrochemical, polymers, pharmacological and agrochemical industry. Moreover, studies in different investigations have been performed in relation to the production of formaldehyde, nitrogen heterocycles, imines, and biochemical systems such as alcohol dehydrogenase, galactose oxidase, and amine oxidase. The oxidative dehydrogenation of amines to produce imines have attracted a great interest within the scientific community because imines can react as electrophiles reductions, condensations, additions and cycloadditions reactions. One of the most important characteristic of oxidative dehydrogenation is its high selectivity to form imines from amines and for that reason several solvents, environmental conditions, metal organic frameworks and metal complexes in conjunction with different transition metals have been used as catalysts for the purposes of increasing the reaction yields. Copper (III) in Cu-BTC and iron (III) in tetracyano(1,2-diamine)ferrate(III) have been used as metallic center in oxidative dehydrogenation of amines because these metals are abundant, cheaper and easily access. In this work, a comparison study between the reaction mechanisms to the imine formation through oxidative dehydrogenation promoted by the coordination of the amine ligand to iron (III) and the catalyzed oxidation of amines by a Cu(II)-MOF was carried out by using geometry optimizations, frequencies and Mülliken charges based on DFT computational calculations. The presence of Fe(III) and Cu(III) as transition metals in tetracyano (1,2-diamine) ferrate(III) and Cu-BTC respectively are the responsible to promote the oxidation of the coordinate amine which influence the imine formation. The results obtained from the DFT simulations for each step of the reaction mechanism of tetracyano (1,2-diamine) ferrate(III) and Cu-BTC reveal that high energies are required to form the imine for each step of the reaction mechanism but Cu- BTC mechanism for the formation of imines was more thermodynamically favored.